Assessing teachers for professional certification the first decade of the National Board for Professional Teaching Standards - Stake, Robert E.; Kushner, Saville; Ingvarson, Lawrence; Hattie, John (Advances in program evaluation ;, 2004)
Nothing is as fundamental to the quality of a school system as the quality of its teachers. For this reason many countries are seeking policies that meet the challenge of promoting quality teaching.The National Board for Professional Teaching Standards (NBPTS) in the USA is the most ambitious and successful attempt by any country to establish a certification system for recognizing and rewarding teachers who reach high professional standards. Established in 1987, the Boards mission has been driven by a simple principle; to place more value on accomplished teaching, we must learn how to evaluate teacher performance in ways that are valid, reliable and fair. By late 2007, over 60,000 teachers had become National Board Certified Teachers. As other countries place increasing importance on policies designed to attract, develop, and retain effective teachers there is growing interest in the extensive research and development work that has underpinned the Boards certification system and guided its implementation. The main purpose of this book is to bring together, for international as well as non-specialist audiences, papers written by the key researchers involved in the development of National Board assessments between 1987 and 1997.One of the many reasons why the Boards work is noteworthy is the extent to which, at every stage of development, it has subjected its standards and certification process to critique by leading figures in educational measurement, as the chapters in this volume illustrate. As a result, the NBPTS has made a major contribution to international understanding about how to develop valid standards and reliable methods for assessing teacher performance that gain both professional and public esteem. The NBPTS provides an example of a well researched certification scheme for measuring teacher quality that can provide a service to governments and employers seeking a reliable indicator of teacher quality. Standards are the gateway to greater professional self-direction, and a certification system is a means by which the teaching profession can build its own infrastructure for defining high quality teaching standards, promoting development toward those standards and providing recognition to those who meet them. This book also aims to provide some of the many lessons the Board has learned about how to make a professional certification system for teachers manageable and affordable, which is perhaps an even greater challenge.This is a special volume focussing on The National Board for Professional Teaching Standards (NBPTS).